The growth performance of Osphronemus goramy reared in saline water with electrical field exposure - Nirmala, Kukuh; Rasmawan, . (Indonesian Society of Scientific Aquaculture (ISSA), 2010)
The aim of this study was to know the optimal salinity level on growth rates of giant gouramy Osphronemus goramy reared in different salinity with electrical field exposure. Four different salinities tested were 0; 3; 6 and 9‰ with the electrical field exposure of 10 Volt. The experiment design was arranged in completely randoumizes design with four treatments and three replications. Stock density was 3 fish/l with mean initial total body length of 7.18±0.30 cm and initial body weight of 5.68±0.67 g. Result of study showed that the treatment of 3‰ shows the best growth performance with specific growth rates of 1.02±0.10% and growth of absolute length of 0.56±0.18 cm. Key words: Salinity, electrical field, growth rate, Osphronemus goramy ABSTRAK Tujuan penelitian ini adalah untuk mengetahui salinitas optimal untuk pertumbuhan ikan gurame Osphronemus goramy yang dipelihara pada media bersalinitas berbeda dengan paparan medan listrik. Perlakuan meliputi empat salinitas media yang berbeda: 0, 3, 6, dan 9‰ dengan paparan medan listrik 10 Volt. Rancangan percobaan yang digunakan adalah rancangan acak lengkap dengan 4 perlakuan dan 3 ulangan. Padat penebaran ikan adalah 3 ekor/l dengan rata-rata panjang total 7,18±0,30 cm dan bobot rata-rata awal 5,68±0,67 g. Hasil penelitian menunjukkan bahwa pertumbuhan ikan gurame terbaik pada penelitian ini dicapai pada salinitas 3‰ dengan pertumbuhan bobot 1,02±0,10% dan pertumbuhan panjang mutlak 0,56±0,18 cm. Kata-kata kunci: Salinitas, medan listrik, laju pertumbuhan, Osphronemus goramy